Case Report: Abemaciclib‐Induced Chronic Renal Failure - Lu Lin; Jinhui Chen; Jing Li; Shuangxin Liu; Weihua Lai (Medicine Advances, 2025)
ABSTRACT Abemaciclib, a cyclin‐dependent kinase 4/6 inhibitor, may induce kidney damage during the treatment of hormone receptor‐positive/human epidermal growth factor receptor 2‐negative breast cancer. We report a case of a 52‐year‐old woman with normal baseline kidney function (serum creatinine, 68.19 μmol/L; eGFR, 89 mL/(min·1.73 m2); blood urea nitrogen, 7.74 mmol/L; cystatin C, 0.74 mg/L) who developed stage 2 chronic kidney disease after 12 months of abemaciclib therapy (150 mg/day, twice daily). Three months after discontinuation, kidney function recovered (serum creatinine, 73.80 μmol/L; normalized cystatin C and uric acid), but creatinine rose again to 92.5 μmol/L within 1 month of reinitiation. This case suggests that long‐term abemaciclib use may lead to kidney damage, potentially progressing to chronic kidney failure. Regular monitoring of renal function indicators is recommended before and during treatment.